2023
DOI: 10.1128/mbio.02990-22
|View full text |Cite
|
Sign up to set email alerts
|

Vitellogenin Facilitates Associations between the Whitefly and a Bacteriocyte Symbiont

Abstract: Intracellular heritable symbionts have been incorporated into insect reproductive and developmental biology by various mechanisms. All Bemisia tabaci species harbor the obligate symbiont Portiera in specialized insect cells called bacteriocytes. We report that the whitefly juvenile hormone and Portiera determined vitellogenin (Vg) localization in bacteriocytes of whiteflies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…This hypothesis gains support from findings indicating that antibiotic-treated beetles, devoid of endosymbionts (Wolbachia and Rickettsia), exhibited delayed egg development in their ovaries (Zchori-Fein, Borad, and Harari 2006). Collectively, these studies provide compelling evidence for the involvement of Wolbachia in both dispersal and egg production processes An intimate interaction between Vitellogenin and endosymbionts is known from several insects (Brumin et al 2020;Guo et al 2018;Mao et al 2020;Sun et al 2023). In whiteflies, for example, Vitellogenin affects fecundity and fitness and the transmission of the endosymbiont, while the endosymbionts affect the transmission of Vitellogenin into the bacteriocytes (Sun et al 2023).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This hypothesis gains support from findings indicating that antibiotic-treated beetles, devoid of endosymbionts (Wolbachia and Rickettsia), exhibited delayed egg development in their ovaries (Zchori-Fein, Borad, and Harari 2006). Collectively, these studies provide compelling evidence for the involvement of Wolbachia in both dispersal and egg production processes An intimate interaction between Vitellogenin and endosymbionts is known from several insects (Brumin et al 2020;Guo et al 2018;Mao et al 2020;Sun et al 2023). In whiteflies, for example, Vitellogenin affects fecundity and fitness and the transmission of the endosymbiont, while the endosymbionts affect the transmission of Vitellogenin into the bacteriocytes (Sun et al 2023).…”
Section: Discussionmentioning
confidence: 62%
“…Collectively, these studies provide compelling evidence for the involvement of Wolbachia in both dispersal and egg production processes An intimate interaction between Vitellogenin and endosymbionts is known from several insects (Brumin et al 2020;Guo et al 2018;Mao et al 2020;Sun et al 2023). In whiteflies, for example, Vitellogenin affects fecundity and fitness and the transmission of the endosymbiont, while the endosymbionts affect the transmission of Vitellogenin into the bacteriocytes (Sun et al 2023). It was also shown that Wolbachia hitchhikes the host's system for transovarial transportation of Vitellogenin in order to enter the ovaries and the oocytes for the bacterium's own propagation (Guo et al 2018).…”
Section: Discussionmentioning
confidence: 90%
“…As an indispensable protein for embryonic development and a key element of vitellogenesis, Vg can be taken up by oocytes through endocytosis regulated by VgR, and provide key nutrients and functional substances for developing embryos [51]. Studies have shown that Vg and VgR are key factors for microorganisms including viruses and bacteria to break through the insect ovarian barrier for maternal transmission [52][53][54]. In RSV-L. striatellus, RNPs, composed of CP, RdRp, and genomic RNA, can bind with Vg produced by haemocyte and enter ovarian germarium nurse cells through VgR-mediated endocytosis to complete vertical transmission [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Some symbionts (e.g., Spiroplasma) use VgR-mediated endocytosis to target oocytes (30). Vg is localized in the bacteriocytes of whiteflies and facilitates the persistence of whitefly-bacteriocyte symbiont associations (107). How Vg impacts the maintenance of most insect-microbe symbioses is not understood.…”
Section: Bacteriocyte Adaptation For Symbiont Transmissionmentioning
confidence: 99%